Self-awarenessin relationto STD/aids, hepatitisand sexual behaviorof university students in São José do Rio Preto, SP - Barbosa, Renata G; Garcia, Fátima CP; Manzato, Antonio José; Martins, Raul A (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: nowadays the dimension of the AIDS epidemy is well-known, but the prevention conducts among university students is a subject not widelystudied. Objective: collect information about young university students concerning their level of awareness in relation to STD/AIDS, Hepatitis B and C.Methods: an anonymous questionnaire was filled in by students from three universities in the city observed. A methodology based on a plan of stratified-randomprobabilistic sampling was used. Results: Eight hundred and eighty-eight questionnaires were answered and 25 were excluded due to inconsistent answers; thetotal number, 75,3% are females and are 24 years old; there is a predominance among these students of heterosexuals, and 81% of them stated that they hadalready started their sexual life; the most important STDs were mentioned by more than 90% of the sampling, and hepatitis B and C were mentioned by 70 to89% of the students. Conclusion: a predominance of women in the sampling of university students researched was found, most of these students have an activesexual life; they have adequate knowledge on contraceptive methods, STD/AIDS, and they also stated that condom is the best prevention method for STD/AIDS; these students started their sexual life around 17 years old, in case of men, and 18 years old in case of women; although 70% of these young studentssaid that they had used condom in their first sexual experience, these figures decreased to 46,1% when it was asked about their present conduct.